HAMBATAN SOSIAL BUDAYA DALAM PENGARUSUTAMAAN GENDER DI INDONESIA (Socio-Cultural Constraints on Gender Mainstreaming in Indonesia) - LESTARI HASTUTI, ENDANG (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005)
Women condition in Indonesia on various aspects of life relatively low. Therefore, gender understanding to improve women roles, both in the household and in the society is required. This paper aims to observe socio-cultural constraints, both internal and external. Research results convinced that women participation in planning and in decision making on development programs in fact lower than men. Even existing culture in certain community give less support and opportunity to women. Women roles between locations differ, similarly existing norms in the community. There are many socio-cultural factors that constraint gender mainstreaming. Women participation in the traditional institutions relatively high. Therefore, gender mainstreaming from the central to local government is very much needed.
Keywords: Socio-Cultural, Cosntrains, Gender Mainstreaming. PENDAHULUAN